Penyuluhan Hukum Tindak Pidana Kekerasan Seksual Bagi Warga Ampel Surabaya - Wahyuni, Silvia Ika Nur; Djawa Mega, Challista Helena Fiorola; Agung, Genzha Nurwahyu; Faria, Milena Miranda; Mone, Simson Efraim Here (Yayasan Daarul Huda Kruengmane, 2025)
The increasing number of sexual violence cases in Indonesia, particularly against women and children, has become a serious issue that requires urgent and collective attention. One of the preventive measures that can be taken is through direct legal education to the community. This study focuses on a legal counseling activity concerning Sexual Violence Crime (Tindak Pidana Kekerasan Seksual/TPKS) delivered to the residents of Ampel Subdistrict, Surabaya. A structured Lesson Plan was developed as a strategic guideline to ensure that learning objectives—covering knowledge, skills, and legal values—could be achieved effectively. The material delivered in the session included the definition and legal basis of sexual violence, its forms, victims’ rights, and the physical and psychological impacts of such crimes, along with appropriate responses. The activity was conducted through several stages: an opening session, presentation of the material, an interactive discussion, and a closing statement. The participants' enthusiastic responses indicated that the legal counseling was successful in enhancing legal awareness and understanding within the community. This activity demonstrated that legal education is not merely about transferring legal norms, but also serves as a transformative social tool capable of shifting public perception regarding sexual violence and the importance of protecting victims. Therefore, implementing legal education based on a structured Lesson Plan may serve as an effective and replicable model to strengthen legal protection for women and children from acts of sexual violence.